Firms’ Environmental Performance : Does News Matter? - Mamingi, Nlandu; Dasgupta, Susmita; Laplante, Benoit; Hong, Jong Ho (World Bank, Washington, DC, 2012)
The empirical literature on environmental performance or compliance has followed two strands: one based on the impact of formal regulation as a means of inducing better environmental performance, and another centered on the role of informal regulation which mainly emphasizes the role of communities and capital markets. The authors analyze the impact of environmental news in print media on firms' environmental performance. Using data from a survey of industrial facilities in the Republic of Korea, probit estimation results indicate that the publication of environmental news in print media and the firm's awareness of this publication are important predictors of a firm's environmental performance, more so than environmental laws, regulations, and environmental training. This paper thus reemphasizes the key role of media in influencing firms' environmental performance.